A proteção do meio ambiente pela atuação do sistema interamericano de direitos humanos - MÜLSTROH, Luciana Monteiro (Universidade Federal do Pará, 2017)
This dissertation has as a background the relationship of environmental protection and Human Rights and aims to highlight how environmental protection comes into action within the work of the Inter-American Human Rights System, from the jurisprudence of the Inter-American Commission on Human Rights and Inter-American Court of Human Rights. Thus, precautionary measures of the Inter-American Commission on Human Rights and judgments of the Inter-American Court of Human Rights covering issues such as indigenous, afro-descendants, defenders of environment and natural resources, as well as and economic, social and cultural rights were selected and analyzed. In this context, the right to healthy environment is stated as a Human Right, which needs to be developed, for the other side increasing attention is focused on the environmental links to Human Rights. Further, this study addresses the issue of environmental conflicts, environmental justice, the integration the protection of Human Rights and environmental concerns well as exposes the functioning of the Inter-American Human Rights System, focusing on the American Convention on Human Rights, the Inter-American Commission on Human Rights and Inter-American Court of Human Rights. Thus, this study considers that the evolutionary and creative interpretation of rights under the American Convention on Human Rights protects the environment, gives an environmental dimension to the Inter-American Human Rights System, recognizes the right to healthy environment and enables Environmental Justice.